Model Evaluasi Pembelajaran pada Masa New Normal: Studi Kasus di SDN 04 Kalisari Kabupaten Grobogan - Nada Nurfadhilah; Ahmad Alkindi Siregar; Vira Muthia Rabi'ah; Burhan Nudin (EL-TARBAWI, 2021)
Since Covid-19, schools implement the online learning system which gives extratasks and responsibilities to all teachers. In online learning, the implementationof formative and summative evaluations has several problems, one of which isthe limitations of media and learning evaluation tools. The purpose of this studyis to explain and analyze (1) the implementation of summative and formativetests before the pandemic (2) the implementation of summative and formativetests during the new normal (3) The obstacles and supporting factors of theevaluation process at SDN 04 Kalisari. The research uses a qualitative approach.The data collection technique was carried out by indirect observation throughthe website, interviews via Zoom, and the study of documentation obtained inthe form of data on school facilities and infrastructure. The technique ofdetermining the informants used purposive sampling, namely the Principal and Teachers. The data analysis technique uses the Miles and Huberman model by means of data reduction, data presentation, and drawing conclusions. The conclusion of this study is that the implementation of formative and summative learning evaluations provides new achievements or new challenges for principals and teachers (1) The use of various learning methods to increasestudent interest (2) Smartphone and unstable network constraints (3) decreasedstudent scores.Keywords: Management; Evaluation; Learning; Pandemic.